Natural phytochemicals and probiotics as bioactive ingredients for functional foods: Extraction, biochemistry and protected-delivery technologies - Silva, Beatriz Vieira da (2018)
he well-known correlation between diet and physiology demonstrates the great possibilities of food to maintain or improve our health, increasing the interest in finding new products with positive physiological effects. Nowadays, one of the top research areas in Food Science and Technology is the extraction and characterization of new natural ingredients with biological activity that can be further incorporated into a functional food, contributing to consumer's well-being. Furthermore, there is a high demand for effective encapsulation methodologies to preserve all the characteristics of bioactive compounds until the physiological action site is reached. Scope and approach: In this review, the relevance of developing standard approaches for the extraction of the highly diverse bioactive compounds was described, as it defines the suitability of the following steps of separation, identification and characterization. Special attention was also dedicated to the encapsulation techniques used on hydrophilic and/or lipophilic compounds (e.g., emulsification, coacervation, supercritical fluid, inclusion complexation, emulsification-solvent evaporation and nanoprecipitation). Key findings and conclusions: Some useful conclusions regarding the selection of the best extraction methodology (Soxhlet extraction, ultrasound-assisted extraction, supercritical fluid extraction, accelerated solvent extraction, or shake extraction) were achieved, considering important aspects such as cost, required technical skills, extract integrity, green chemistry principles, solvent type, sample size, pH, temperature and pressure. In addition, this comprehensive review allowed defining the best protective approach to solve the limitations related to the extremely low absorption and bioavailability of bioactive phytochemicals, overcoming problems related to their low solubility, poor stability, low permeability and metabolic processes in the GI tract.